The Effect of Emotional Intelligence and Social Support on Anxiety in Primigravida Pregnant Women in The Third Trimester in Facing Childbirth - Naimah, Hayatun; Alfiani, Desi Rusiana; Marissa, Aski (Devotion : Journal of Research and Community Service, 2025)
ABSTRACTAnxiety during the third trimester of pregnancy is a significant concern, especially among primigravida women with no previous childbirth experience. This research explores the influence of emotional intelligence and social support on anxiety levels in third-trimester primigravida pregnant women. This research employed a quantitative method and purposive sampling, collecting data from 71 respondents who met specific inclusion criteria. Standardized instruments were employed, including the Pregnancy-related Anxiety Scale (PrAS), the Wong and Law Emotional Intelligence Scale (WLEIS), and the Social Provisions Scale (SPS). Multiple regression analysis revealed that emotional intelligence and social support together accounted for 18.2% of the variance in anxiety (p ≤ 0.01). Individually, emotional intelligence contributed 11.9% and social support 12.2% to the reduction of anxiety, suggesting that social support had a slightly greater impact. These findings highlight the importance of enhancing both internal and external coping resources in maternal care. The study contributes to developmental and clinical psychology by refining the understanding of psychological determinants of prenatal anxiety and reinforces the role of social networks in maternal mental health. Practically, it underscores the need for tailored emotional regulation training and structured support systems for first-time mothers. Future studies are recommended to explore additional psychological and contextual factors influencing prenatal anxiety through longitudinal or intervention-based designs.